2017
DOI: 10.3847/1538-4357/aa8863
|View full text |Cite
|
Sign up to set email alerts
|

The HDUV Survey: Six Lyman Continuum Emitter Candidates at z ∼ 2 Revealed by HST UV Imaging*

Abstract: We present six galaxies at z 2 that show evidence of Lyman continuum (LyC) emission based on the newly acquired UV imaging of the Hubble Deep UV legacy survey (HDUV) conducted with the WFC3/UVIS camera on the Hubble Space Telescope (HST). At the redshift of these sources, the HDUV F275W images partially probe the ionizing continuum. By exploiting the HST multiwavelength data available in the HDUV/GOODS fields, models of the UV spectral energy distributions, and detailed Monte Carlo simulations of the intergala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 113 publications
8
45
0
Order By: Relevance
“…The depths of the F275W and F336W bands are 27.6 and 28.0 (5σ), respectively. The deep F275W and F336W images from the HDUV survey have been used to study the LyC escape fraction in galaxies at z ∼ 2 and z ∼ 3, respectively (Naidu et al 2017;Rutkowski et al 2017;Japelj et al 2017). In particular, Japelj et al (2017) studied the LyC escape fraction in a sample of galaxies at z = 3 − 4 selected in 9 arcmin 2 MUSE HUDF survey field using the HDUV F336W image and found the relative escape fraction f esc,rel < 0.6 for galaxies with 0.1L * .…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depths of the F275W and F336W bands are 27.6 and 28.0 (5σ), respectively. The deep F275W and F336W images from the HDUV survey have been used to study the LyC escape fraction in galaxies at z ∼ 2 and z ∼ 3, respectively (Naidu et al 2017;Rutkowski et al 2017;Japelj et al 2017). In particular, Japelj et al (2017) studied the LyC escape fraction in a sample of galaxies at z = 3 − 4 selected in 9 arcmin 2 MUSE HUDF survey field using the HDUV F336W image and found the relative escape fraction f esc,rel < 0.6 for galaxies with 0.1L * .…”
Section: Sample Selectionmentioning
confidence: 99%
“…Thus we have to infer the LyC escape in the galaxies at the epoch of the reioisation based on either directly measuring LyC escape fraction in galaxies at lower redshift or correlating galaxy spatial positions with the Lyman alpha forest at z > 6 (e.g., Kakiichi et al 2018). In the last decade, people have conducted extensive studies of LyC escape fraction in galaxies at z < 4 using a number of different approaches, including the rest-frame ultraviolet spectroscopy (e.g., Leitet et al 2013;Leitherer et al 2016;Izotov et al 2016b,a;Steidel et al 2001Steidel et al , 2018Shapley et al 2006Shapley et al , 2016Nestor et al 2013) and narrow/intermediate/broad-band UV imaging (e.g., Siana et al 2007Siana et al , 2015Vanzella et al 2010Vanzella et al , 2016Nestor et al 2011;Cooke et al 2014;Rutkowski et al 2016Rutkowski et al , 2017Vasei et al 2016;Bian et al 2017;Japelj et al 2017;Naidu et al 2017;Fletcher et al 2018;Ji et al 2019). However, accurately measuring the escape fraction remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware that different works predict very different escape fractions for Lyα (e.g. Wofford et al 2013;Naidu et al 2017, but we choose to follow the trend observed in Hayes et al (2011). Predicting the spatial and spectral profiles of such emission would require the full calculation from radiative transfer techniques (Verhamme et al 2006(Verhamme et al , 2012Rosdahl et al 2013;Lake et al 2015), which is beyond the scope of this work.…”
Section: Lyα Scattering From Nearby Stellar Continuummentioning
confidence: 99%
“…Motivated in part by almost all confirmed LyC leakers to date (green stars) showing higher ΣSFR than the average at their redshifts, in our Model II we link fesc to ΣSFR (see §4). The green stars represent leakers presented byNaidu et al (2017); de Barros et al (2016); Vanzella et al (2016, 2018); Shapley et al (2016); Bian et al (2017); Matthee et al (2018); Borthakur et al (2014); Leitherer et al (2016); Izotov et al (2016a,b, 2018a,b); Leethochawalit et al (2016); Jones et al (2013);…”
mentioning
confidence: 99%